Measuring Armour Layer Erosion in Scale Model Tests - Lemos, R. (2011)
In Portugal, rubble-mound breakwaters are a very common harbour protection structure. Since this is a sort of structure where repair or maintenance works may have to be carried out during its lifetime, there has been some effort in the definition of suitable procedures to forecast the need for such works. One of these procedures involves the time evolution of the armour layer erosion and the definition of a dimensionless quantity called the damage of the structure. Melby (1999) presented a formula for predicting the damage evolution of rubble mound breakwaters, based on the incident wave characteristics. This paper presents the results of a study that aimed at assessing the applicability of those formulae for wave conditions different from the ones of the tests of Melby (1999), but using the same kind of long-term scale model tests. In such tests sequences of stationary sea states hit the armour layer and the eroded volume is measured at the end of every two sea states. This measurement of the eroded volume was carried out using a technique based upon the reconstruction of stereo pairs, in which, refraction due to the air-water interface, is corrected. This was the first time this survey technique was used intensively in such long-term scale models and it aimed at assessing the technique performance in scale model tests where intensive profile surveying is necessary